The Process Of Integration And Globalization In All Aspects Of Economic Society (Texas Journal of Multidisciplinary Studies, 2022)
This research paper is totally devoted to the deep analysis of how the integration and globalization process between the economic societies by all aspects. These processes are manifested in the deepening of the international division of labor, the internationalization of economic life, their interdependence and convergence, the development and strengthening of regional international systems.